O ensino de história para apenados(as) em Santa Maria: a construção de vivências históricas de apenados(as) nos presídios em Santa Maria e suas vivências históricas - Schirmer, Janete Teresinha (2016)
Imprisonment has always been used by mankind. From the shackles and cages of primitive peoples, past the Brazen Bull of the Greeks, where they confined the condemned in a kind of chamber over the fire, and the Roman cages, for the crows to devour the condemned then used extensively during the Inquisition in the Middle Ages to reach modern Austrian luxury prisons: society has always sought to eliminate offenders from social life. During the early and Greco- Roman period, this served much more to arrest and punish slaves of dominated peoples, but also to offenders of established social agreements, as laws, and in the Inquisition to obtain the confession of considered heretics. Later, during the Enlightenment, Rationalism and Humanism came to question the situation of man before the world and strongly criticize existing methods of penalties. The imprisonment itself arose, although under the same logic of keeping criminals away from social life and using it as a way to drive out miserable people, prostitutes and others who would not need this kind of withdrawal from society. With the Modern and Contemporary ages, new thoughts about how treatment should be with the grieving ones came to the social debate. The Declaration of the Rights of Man and of the Citizen, with the postwar democratic constitutions, have brought new legal orders regarding crimes and their criminal charges. Prisoners, above all, came to be seen as a Human Being, subject to legal punishments provided in specialized codes for these purposes, but with rights. The Brazilian Federal Constitution expressly provides for the State’s responsibility towards all citizens, and must guarantee fundamental rights; it also should cover inmates who are or will join the penitentiary system. To those condemned, conditions must be provided for their social reintegration and nonviolation of their rights as human beings. Thus, theses have emerged, such as resocialization, commutation of sentences, possibility of progression of regimes in order to reduce the time of compliance with sanctions and stay in prisons. Another very positive action is to institute access to formal education aimed at re-education of the victims. The Law on Criminal Executions (LEP) has attempted to fulfill two basic purposes: to enforce what the sentence or criminal decision provides and to create opportunities and means for the victims to participate in social reintegration. Thus, formal teaching in prisons and teaching history in particular have contributed to these purposes. Due to the fact that few works refer to the teaching of History in prisons, and being the field of our work, this work is the result of an action taken in History classes of the Julieta Balestro School in the Regional Prison of Santa Maria (PRSM) and State Prison of Santa Maria (PESM), in RS. The central idea is that inmates reconstruct their life histories, aiming, through the narratives, to have insights of the moment and historical reality. Although not exclusive, the work done does not focus on cognitive and psychological aspects, focusing only on historical issues of inmates’s narratives.